Only Vimal Campaign - Reliance Industries Limited (2023)
In 1978, Vimal was rebranded as Only Vimal, and through an innovative advertising campaign, it was marketed as a premium fabric brand for the youth. In 1979, Shri Dhirubhai Ambani organized the first Vimal fashion show. Vimal became the one-stop destination for the average Indian family's textile purchases: shirting, suiting, saris, dress materials, and furnishing fabrics.